Traditional Chikitsa Upkrama on Daivavyapashraya: A Brief Review Study - Aggarwal, Suman; Aggarwal, Vaidya Sandeep; Patel, Shambhu P; Kumar, Sujit (International Research Journal of Ayurveda & Yoga, 2021)
The Daivavyapashraya Chikitsa (divine therapy) is one of the most underappreciated ways of therapy, and many illnesses are not healed at their source. The success rate of therapy will be improved if a balanced approach is used that involves all Trividha Chikitsa. Daivavyapashraya Chikitsa (divine therapy) is performed in numerous parts of the world, consciously or unknowingly, as a part of religious traditions, but it goes beyond that and emphasizes on Spirituality. As a result, recording of certain traditions that are quickly becoming obsolete, as well as a comprehensive analysis of Daivavyapashraya Chikitsa (divine therapy), are necessary. In this article, an attempt is made to explore the concept of Daivavyapashraya Chikitsa (divine therapy).